VD_FINDINFO AI 321/20 - 203/2021 vom 9. Juli 2021 - VD Tribunal cantonal (2021)
DEGRÉ DE L'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, MEMBRE D'UNE COMMUNAUTÉ RELIGIEUSE | 28a al. 2 LAI, 4 LAI, 8 al. 3 LPGA, 27 RAI